Why are health and sickness socially patterned across human societies? The embodiment dynamic over the life course - Michelle Kelly-Irving (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This paper is based on a keynote address at the Société d’Anthropologie de Paris conference in 2021. It refers to research stemming from the field of social epidemiology, specifically addressing the issue of health inequalities. The unequal distribution of health across social-structural groups in the population is nothing new, and continues to be a persistent problem in public health. Understanding how social inequalities relate to health inequalities, how processes and mechanisms operate over the life course to create health inequalities, is an interdisciplinary endeavour that combines the social and biomedical sciences. In this paper I outline recent theoretical and empirical work that aims to unravel how 'the social becomes biological' through the embodiment dynamic, leading, at least in part, to social and socioeconomic gradients in many health outcomes.